Theoretical-Methodological Importance of International Listing of Stocks for Investors and Emitents - Мазур, Ірина Іванівна; Сазонов, Р. (Київський національний університет імені Тараса Шевченка, 2018)
Досліджено подвійний лістинг акцій компаній; розкрито умови, за яких міжнародний лістинг акцій компаній стає одним із найдоречніших способів фінансування бізнесу; виявлено вплив міжнародного лістингу акцій компаній на ліквідність акцій на внутрішньому ринку, збільшення обсягу торгів акціями компанії; запропоновано українським акціонерним компаніям використовувати міжнародний лістинг для збільшення своєї капіталізації.

In the conditions of globalization of the economic environment, the integration processes of the international capital markets are intensifying, which envisages the possibility of placing securities in foreign markets. This gives some benefits to national investors and issuers. These benefits include: scaling up the attraction of investors' financial resources; strengthening of the business reputation and issuer's credit rating; Successful placement of shares in the international market contributes to the increase of profits. International listing of shares increases the prestige and image of the issuer. The main motivation of most companies entering the foreign capital markets is only financial - they plan to increase their capital in the markets of highly developed countries and increase the liquidity of their shares. International listing provides new markets for more active securities that do not require detailed reporting and have significant liquidity. In some cases, the introduction of international listing increases the value of the company's shares. As a rule, this happens more often in the US, when the market value of shares is higher than that existing on the issuer's market. Moreover, the fact of an increase in the number of investors who buys company shares increases the liquidity of shares, narrowing the spread. That is, the main motive for stock quotes abroad is to increase the value of its capital and liquidity of shares, which will eventually give an opportunity to attract additional capital. All this contributes to the growth of the number of national companies that market their shares on foreign stock exchanges. Investigated double listingof shares of companies; discloses the conditions under which the international listing of shares of companies becomes one of the most appropriate ways of financing business; the influence of international listing of companies' shares on the liquidity of shares in the domestic market, increase of trading volume of shares of the company was revealed; invited Ukrainian joint-stock companies to use the international listing to increase their capitalization.
Теоретико-методологічне значення міжнародного лістингу акцій для інвесторів та емітентів
Keywords: акція; міжнародний лістинг; фондова біржа; ліквідність; спред; stock; international listing; Stock Exchange; liquidity; spread